INTERNALISASI NILAI-NILAI PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK AKHLAKUL KARIMAH PESERTA DIDIK DI MTS RAUDHATUL ULUM KARANGPLOSO - Khairul Rofiah; Azhar Haq; Lia Nur Atiqoh Bela Dina (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
Internalization of value is the process of making value as part of a person, the process will be created when created atmosphere, environment and human interaction that allows the process of socialization and interaction of values. Internalization of values in Islamic religious education is the formation of one's self that will create morality. MTs Raudhatul Ulum Karangploso was targeted by the research. This study uses qualitative research based on phenomenology using case study research. By using interactive strategies such as direct observation, participatory observation, in-depth interviews, documents, photos and voice recordings and other data that can support the continuity of this research in order to obtain valid data. In the application of internalization of islamic religious education values in shaping the ability of students in MTs Raudhatul Ulum Karangploso, what needs to be considered is the role of teachers in internalizing the values of Islamic religious education in shaping student morality, methods used by teachers, supporting factors, obstacles and solutions for students. Not only the role of the teacher, the role of parents is also important in shaping the morality of students.